Hotel Efficiency Measurement in The Most Economically Sustainable Regions by Using Data Envelopment Analysis - Vahedi, Sina (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
In the past decade, sustainability trend has been increasingly applied by most of the countries around the world. As a result, all countries in the United Nations have decided to formulate sustainability into a framework by introducing sustainable development goals (SDG) in 2015. SDG consists of 17 goals to cover all the aspects of the sustainability such as environmental, social and economic sustainability. These goals are not only a great instruction for countries to apply sustainability, also it can help countries to evaluate and estimate their successfulness of sustainability in different organizations and businesses. SDG 8 (decent work and economic growth) as one of the most important indicators , shows the successfulness of each country to achieve a sustainable economy. Since creation of SDG concept, there were many studies that they measured successfulness of businesses efficiencies according to these goals. However, there are few studies that they evaluate hotel industry’s financial efficiency in parallel of SDG 8. As a result, this thesis is going to investigate parallel success of efficient countries in economic sustainability, and financial efficiency of their hotel industry. To measure the financial efficiency, this study applied Data Envelopment Analysis (DEA) to benchmark countries in 2017 and 2018. “Number of rooms” and “Number of employees” as inputs and “RevPAR” and “Occupancy rate” as outputs have been selected to analyze hotel’s financial efficiencies. The analysis of this study showed that 5 countries (Estonia, Netherlands, New Zealand, Switzerland and United States) were fully financial efficient in hotel industry. Based on the study’s result, recommendations for policy makers and possible future studies have been illustrated accordingly.

ÖZ : Son on yılda, sürdürülebilirlik trendi dünyadaki çoğu ülke tarafından giderek daha fazla uygulanmaktadır. Sonuç olarak, Birleşmiş Milletler bünyesindeki tüm ülkeler 2015 yılında sürdürülebilir kalkınma hedeflerini (SKH) ortaya koyarak sürdürülebilirliği bir çerçeveye oturtmaya karar vermişlerdir. SKH, sürdürülebilirliğin çevresel, sosyal ve ekonomik sürdürülebilirlik gibi tüm yönlerini kapsayan 17 hedeften oluşmaktadır. Bu hedefler, sadece ülkeler için sürdürülebilirliği uygulamak için eşsiz bir fırsat değil, aynı zamanda ülkelerin farklı organizasyon ve işletmelerde sürdürülebilirlik konusundaki başarılarını değerlendirmelerine ve tahmin etmelerine yardımcı olabilmektedir. En önemli göstergelerden biri olan SKH 8 (insana yaraşır iş ve ekonomik büyüme), her ülkenin sürdürülebilir bir ekonomiye ulaşmadaki başarısını göstermektedir. SKH kavramının oluşturulmasından bu yana, işletmelerin verimliliklerinin bu hedeflere göre başarısını ölçen birçok çalışma icra edilmiştir. Ancak otel sektörünün finansal etkinliğini (SKH 8) değerlendiren az sayıda çalışma bulunmaktadır. Sonuç olarak, bu tez ekonomik sürdürülebilirlik konusunda etkin ülkelerin paralel başarılarını ve otel sektörünün finansal verimliliğini araştıracaktır. Bu çalışmada finansal verimliliği ölçmek için 2017 ve 2018 yıllarında karşılaştırma yapılan ülkelere Veri Zarflama Analizi (VZA) uygulanmıştır. Otellerin finansal verimliliklerini analiz etmek için, girdi olarak “Oda sayısı” ve “Çalışan sayısı”, çıktı olarak “Oda başına günlük gelir” ve “Doluluk oranı” seçilmiştir. Bu çalışmanın analizi, 5 ülkenin (Estonya, Hollanda, Yeni Zelanda, İsviçre ve Amerika Birleşik Devletleri) otelcilik sektöründe tam finansal etkinliğe sahip olduğunu göstermiştir. Çalışmanın sonucuna dayalı olarak, politika oluşturucular ve sektör profesyonelleri için öneriler ve gelecekteki çalışmalar bu doğrultuda aktarılmıştır.
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2023. Supervisor: Assoc. Prof. Dr. Mine Haktanır.
Keywords: Thesis Tez; Tourism Faculty; Tourism--Hospitality Industry--Hotel Efficiency Measurement; Hotel financial efficiency; Data envelopment analysis; Decent work and economic growth; Sustainable development goals; SDG 8